Comprehensive understandings on the high dielectric constant insulating layers for alternating-current thin-film electroluminescent devices - Lee, YH; Ju, BK; Kim, DH; Oh, MH (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2001)
We introduced thin-film electroluminescent cells (TFEL) with a new multilayered-BaTiO3 layer for the low-voltage driven devices. We begin by simulating the basic parameters for TFEL devices in eletrostatic boundary condition and point out how the insulator parameters influences on the typical operating properties of the devices. Next, we performed the voltage accelerated breakdown testing of the multilayered-BaTiO3 having both high dielectric constant and high breakdown strength. The time-zero-breakdown distribution is shown to be dependent on surface roughness, while the long-term failure studied by time-dependent-dielectric breakdown technique at high field is dependent on the bulk characteristics, i,e,, transition layers within m-BT films. Thirdly, the TFEL, devices were prepared using the multilayered-BaTiO3 as dielectric materials. We observed a decrease of turn-on voltage with increasing thickness and the increase of the maximum over voltage. Finally, typical symmetric capacitance-voltage (C-V) and internal charge-phosphor field characteristics were obtained for the device with thin m-BT layers. With increasing thickness of m-BT the significant asymmetry with respect to the applied voltage polarity was observed. This is a main difference as compared with the symmetric characteristics of conventional TFEL devices with low dielectric constant insulators. The experimental results indicate the fact that a selection of the thickness of upper m-BT and their deposition process would strongly affect the interfacial characteristics as well as hulk characteristics of an as-grown ZnS :Pr, Ce layer.
Keywords: BREAKDOWN